Création et compétences du Tribunal pénal international pour l'ex-Yougoslavie - Hajam, Mohamed (Études internationales, 1995)
The Security Council adopted Resolution 808 on February 22, 1993. This resolution created an international tribunal to judge people presumed responsible for grave breaches of humanitarian law committed on the territory of the former Yugoslavia since 1991. The tribunal's status is defined by Resolution 827, whereby its jurisdiction covers all serious violations committed by individuals in the former Yugoslavia. The principle nullum crimen, nulla poena sine lege is fully respected. The tribunal's effectiveness, however, depends on the rulings the judges will hand down and on support from all states. Creating the ICT has been deemed a very important step. By judging criminals, the tribunal not only hopes to introduce the idea of justice into a sphere of international life dominated by power relationships, but also wishes especially to dampen the victors' feeling of impunity. AU of this requires one thing : the goodwill of the states so that this tribunal may carry out its task.